Gaining competitive advantage in the gray zone response options for coercive aggression below the threshold of major war - Morris, Lyle J.; Mazarr, Michael J. 1965-; Hornung, Jeffrey; Pézard, Stéphanie; Binnendijk, Anika; Kepe, Marta (RAND Corporation, 2019)
The United States is entering a period of intensifying strategic competition with several rivals, most notably Russia and China. U.S. officials expect this competition to be played out primarily below the threshold of armed conflict, in what is sometimes termed the gray zone between peace and war. In this report, the authors examine how the United States might respond to Russian and Chinese efforts to seek strategic advantage through coercive actions in the gray zone, including military, diplomatic, informational, and economic tactics. The United States is ill prepared and poorly organized to compete in this space, yet the authors' findings suggest that the United States can begin to treat the ongoing gray zone competition as an opportunity more than a risk. Moreover, leaders in Europe and Asia view Russian and Chinese gray zone aggression as a meaningful threat and are receptive to U.S. assistance in mitigating it. In this report, the authors use insights from their extensive field research in affected countries, as well as general research into the literature on the gray zone phenomenon, to sketch out the elements of a strategic response to the gray zone challenge and develop a menu of response options for U.S. officials to consider
Keywords: Militärpolitik; Kriegführung; Cyberspace; China; USA; Russland; Cyberspace operations (Military science); United States; Russia (Federation)